The financial sustainability of the World Health Organization and the political economy of global health governance: a review of funding proposals - Srikanth K. Reddy; Sumaira Mazhar; Raphael Lencucha (BMC, 2018)
Abstract The World Health Organization (WHO) continues to experience immense financial stress. The precarious financial situation of the WHO has given rise to extensive dialogue and debate. This dialogue has generated diverse technical proposals to remedy the financial woes of the WHO and is intimately tied to existential questions about the future of the WHO in global health governance. In this paper, we review, categorize, and synthesize the proposals for financial reform of the WHO. It appears that less contentious issues, such as convening financing dialogue and establishing a health emergency programme, received consensus from member states. However, member states are reluctant to increase the assessed annual contributions to the WHO, which weakens the prospect for greater autonomy for the organisation. The WHO remains largely supported by earmarked voluntary contributions from states and non-state actors. We argue that while financial reform requires institutional changes to enhance transparency, accountability and efficiency, it is also deeply tied to the political economy of state sovereignty and ideas about the leadership role of the WHO in a crowded global health governance context.